Thermodynamic studies on single-crystalline Gd2BaNiO5 - Popova, Elena; Klingeler, Rüdiger (Physical review. B, Condensed matter and materials physics, 2012)
We present the thermodynamic properties and the magnetic phase diagram of Gd2BaNiO5 investigated by means of specific heat and magnetization measurements performed along the main crystallographic axes of the single crystal. Our data imply antiferromagnetic ordering at TN = 55 K and a spontaneous spin-reorientation transition at TSR = 24 K. Upon application of external magnetic fields, a spin-flop transition is observed at T < TSR in magnetic fields B ∥ b axis and at TSR < T < TN in magnetic fields B ∥ a axis. The magnetic phase diagram in Gd2BaNiO5 is established from these data. Considering Gd-Gd and Gd-Ni interactions allows estimating the magnetic contribution of the gadolinium subsystem to the magnetization and the specific heat. The Gd-Gd interaction is organized via Ni chains being therefore sensitive to the angle between Gd and Ni magnetic moments. The analysis of the experimental data shows that the behavior of the nickel subsystem differs from that of a classical antiferromagnet.